TRIM25 in the Regulation of the Antiviral Innate Immunity - Martín-Vicente, María; Medrano, Luz M.; Resino, Salvador; García-Sastre, Adolfo; Martínez, Isidoro (Frontiers in Immunology, 2017)
TRIM25 is an E3-ubiquitin ligase enzyme that is involved in various cellular processes, including regulation of the innate immune response against viruses. TRIM25-mediated ubiquitination of the cytosolic pattern recognition receptor RIG-I is an essential step for initiation of the intracellular antiviral response and has been thoroughly documented. In recent years however, additional roles of TRIM25 in early innate immunity are emerging, including negative regulation of RIG-I, activation of the MDA5-MAVS-TRAF6 antiviral axis and modulation of p53 levels and activity. In addition, the ability of TRIM25 to bind RNA may uncover new mechanisms by which this molecule regulates intracellular signaling and/or RNA virus replication.